Kesehatan Tenggorok pada Siswa di Sekolah Dasar Negeri 11 Manado - Solossa, Novita; Mengko, Steward K.; Tamus, Agustien Y. (Universitas Sam Ratulangi, 2021)
Abstract: Health problems such as throat disease can be caused by various factors either external or internal. This study was aimed to obtain a description of throat health status of students at Sekolah Dasar Negeri 11 (Public Elementary School) Manado. This was a descriptive and observational study with a cross sectional design. There were a total of 25 male and female students. The results showed that 25 students (100%) had normal tonsil color; 24 students (96%) had normal tonsil surface and one student (4%) had pathological tonsil surface; 22 students (88%) had normal tonsil size and three students (12%) had pathological tonsil size. There were 25 students (100%) who had normal results on examination of pharynx both mucosa and the back wall of pharynx. In conclusion, most students of SDN 11 Manado had normal throat health status.Keywords: throat health status; elementary students Abstrak: Masalah kesehatan seperti penyakit tenggorok dapat disebabkan oleh berbagai faktor baik eksternal maupun internal. Penelitian ini bertujuan untuk mendapatkan gambaran kesehatan tenggorok siswa Sekolah Dasar Negeri 11 Manado. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Jumlah total keseluruhan subyek penelitian ialah 25 siswa. Hasil penelitian mendapatkan sebanyak 25 siswa (100%) dengan warna tonsil normal; 24 siswa (96%) dengan permukaan tonsil normal dan satu siswa (4%) dengan permukaan tonsil patologik; 22 siswa (88%) dengan ukuran tonsil normal dan 3 siswa (12%) lainnya dengan ukuran tonsil patologik. Sebanyak 25 siswa (100%) dengan hasil normal pada pemeriksaan faring baik mukosa maupun dinding belakang faring. Simpulan penelitian ini ialah sebagian besar siswa SDN 11 Manado memiliki gambaran kesehatan tenggorokan yang normal.Kata kunci: kesehatan tenggorok; siswa Sekolah Dasar